2018
DOI: 10.1002/pds.4676
|View full text |Cite
|
Sign up to set email alerts
|

Comparing drug effectiveness in children: A systematic review

Abstract: Purpose: The purpose of the study is to assess the current state of the art in pediatric comparative effectiveness research, potential gaps, and areas for improvement.Methods: Relevant articles from inception to February 2015 were retrieved from Embase and Medline. We sequentially screened titles, abstracts, and full texts, with independent validation. Data regarding general information and study methods including statistical analysis were extracted. Study quality was assessed using Newcastle-Ottawa Scale (NOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Despite the limitations of our search strategy, we note that our yield (29 eligible studies out of 915 unique citations) was 3.2%, comparable to that obtained in a recent systematic review on a similar topic. Dukanovic et al, in a review of comparative effectiveness studies in children, found that 4.2% of the studies were eligible (164/3926; the large denominator here reflects their inclusion of studies from the inception of Embase and Medline) [69]. While comparative effectiveness is not the same topic as RWE, it may be similar enough to provide an indication of a reasonable yield for most search strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limitations of our search strategy, we note that our yield (29 eligible studies out of 915 unique citations) was 3.2%, comparable to that obtained in a recent systematic review on a similar topic. Dukanovic et al, in a review of comparative effectiveness studies in children, found that 4.2% of the studies were eligible (164/3926; the large denominator here reflects their inclusion of studies from the inception of Embase and Medline) [69]. While comparative effectiveness is not the same topic as RWE, it may be similar enough to provide an indication of a reasonable yield for most search strategies.…”
Section: Discussionmentioning
confidence: 99%